New VAT Rules for E-commerce: What Will They Bring to Public Budgets? - Kristýna Kebrtová; Hana Zídková (European Financial and Accounting Journal, 2022)
The article focuses on the new rules for electronic commerce that came into force on 1 July 2021 in all EU Member States. The main goal is to explain these new rules of taxation of consignments of goods from abroad (both from the European Union and third countries) to non-taxable persons and subsequently to calculate the impact of these new rules on the tax revenues of public budgets of the Czech Republic. The assumption set in advance is that the changes in tax legislation will result in an increase in the Czech public budget revenues due to the boosted revenues from value-added tax collected on foreign shipments. Year-on-year, tax revenues from online purchases will undoubtedly increase also due to the growing popularity of online shopping, currently sustained by the ongoing pandemic situation of covid-19. The calculations of the additional value-added tax revenue are based mainly on the data sourced from the Czech Statistical Office and a study carried out for the European Commission. The additional value-added tax revenue is calculated using the three model situations that assess impacts on the tax revenue of public budgets in the Czech Republic. For 2019, these impacts were estimated at between CZK 3.1 and CZK 6.1 billion.
Keywords: H21; H26; K34; 650; Value-Added Tax; Distance Sale of Goods; Additional VAT Revenue; One Stop Shop